The Effects of Promoting Nursing Practice Guidelines to Prevent Ventilator-Associated Pneumonia in Newborns in the Pediatric and Neonatal Intensive Care Unit Nan Hospital - Thiwannalak, Wasinee (Journal of Nurses Association of Thailand Northern Office, 2025)
This participatory action research aimed to explore the effects of using nursing practice guidelines to prevent ventilator-associated pneumonia in newborns on the levels of knowledge and practices in professional nurses regarding the prevention and the incidence of ventilator-associated pneumonia among newborns in the Pediatric and Neonatal Intensive Care Units, Nan Hospital. The study comprised 4 stages; planning, implementation, observation, and reflection. The samples were 13 professional nurses and 70 newborns. Data were collected from September 2024 to March 2025. The research instruments were the intervention instruments and the data collection instruments. Data were analyzed using descriptive statistics, independent t-tests, and chi-square tests. The results demonstrated that after using the nursing practice guidelines for the prevention of ventilator-associated pneumonia, the average score of nurses’ knowledge regarding the prevention of ventilator-associated pneumonia in newborns was statistically significant higher than before using the nursing practice guidelines (t=7.104, p<.001). The nurses also performed a higher correct practice (X2 =251.682, p<.001). The incidence of ventilator-associated pneumonia in newborns decreased statistically and significant decreased from 11.24 to 3.46 episodes per 1,000 days of intubation (X2=3.231, p=.036). Therefore, using the nursing practice guidelines regarding the prevention of ventilator-associated pneumonia in newborn enhanced the knowledge and practices among professional nurses and reduced the incidence of ventilator-associated pneumonia among newborns.